IMPLEMENTASI HASIL MUSRENBANG DI KOTA PEKANBARU - Nurmasari, Nurmasari; Suri, Dia Meirina (UIR PRESS, 2017)
Participatory development takes effect since in the regional autonomy policy, participatory development gives more opportunity to the community to take an active role in doing development, the aim is for the development done directly to meet the needs of the community. The participatory process begins with a meeting between the community and the government called the Development Planning Deliberation or abbreviated with Musrenbang, the result of this Musrenbang which is then used as a guide in preparing the development program, in addition to the planning process, the community is also involved in the implementation process up to the evaluation of development outcomes .This study aims to find out and analyze how the implementation of Musrenbang results, to know and analyze the factors that influence the implementation of Musrenbang results. This research was conducted in Pekanbaru City with research time for one year, key informant in research is Head of Finance Section of Bappeda Pekanbaru, Responsible Activity of Musrenbang Year 2015, Finance Section of BPKAD Pekanbaru City, Musrenbang District level.Leather data analysis is done by triangulation of data source with data reduction step, data presentation, data withdrawal and verification. From the results of this study want to know and analyze the implementation of Musrenbang results and find and analyze the factors that affect the implementation of Musrenbang results. The result of the research finds that the implementation of Musrenbang result starts with several stages, that is done at kelurahan level which the result is then brought to be gathered at Musrenbang Kecamatan level, the result of the meeting at the kelurahan level is adjusted with the activity plan which has become the work plan of SKPD Kecamatan and adjusted to the budget, the result of Musrenbang Kecamatan then forwarded to Musrenbang tingka Kota. The results of this Municipal level musrenbang which later became the Local Government Work Plan.Musrenbang Results 2015, there are 1273 development programs proposed by 12 Sub-districts in Pekanbaru City, but many of these proposals can not be implemented, this is because the government prioritizes priority programs in accordance with RKPD documents and national development programs.Factors affecting the Implementation of Musrenbang Outcomes are the lack of commitment from local governments in implementing Musrenbang decisions and funding or budgetary problems contained in the APBD.